Management of Anesthesia in Pediatric Patients with Bronchoscopy Late Onset Foreign Body Aspiration - Sintani, Rinni; Vitraludyono, Rudy (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Aspiration of foreign bodies in the airways is a severe and fatal condition if it occurs in children, because the risk of life-threatening obstruction is higher. Bronchoscopy is the main choice of procedure for treating foreign body aspiration, either with rigid bronchoscopy or flexible bronchoscopy. Anesthesia techniques are used with comprehensive anesthesia considerations, such as premedication, induction of anesthesia, maintenance of anesthesia, and monitoring. Objective: To evaluate the management of anesthesia in a pediatric patient with foreign body aspiration in late-onset settings. Case report: We report a case of anesthesia management in a child who aspirated a foreign body (peanuts) three days before being delivered to the hospital and undergoing a rigid bronchoscopy procedure. The patient experienced respiratory failure, and atelectasis was found in the right lower lobe of the lung upon arrival at the Emergency Unit (ER) due to the late onset of the case, so a secure airway must be performed before rigid bronchoscopy. Post-treatment care is carried out by observation and monitoring in the Intensive Care Unit (ICU) with complications of pneumonia. After three days of ICU treatment, the patient was transferred to the High Care Unit (HCU) in improved condition. The patient was discharged after three days of treatment in the low care Unit. Conclusion: Rigid bronchoscopy is the best modality for extracting foreign bodies in the pediatric airway. Delayed onset effects from foreign body aspiration in the respiratory tract cause greater complications after bronchoscopy. Pneumonia is the most common complication. Comprehensive anesthesia evaluation and preparation are the keys to the success of this procedure.